Fracture analysis of tapered pin loaded lugs using boundary element methods - Chew, Bryan Pei En (2018)
In this study, the fracture analysis of cracks in tapered pin loaded lugs was carried out using the Boundary Element Method (BEM). This study analyses lugs with a tapered geometry and how the effects of varying geometrical features such as taper angle, outer-to-inner radius ratio, and the loadings from different orientations affects stress concentration and stress intensity. This study first assesses the location of the highest stress point when three different loadings (0, 45, 90 degree) are applied in three different Ro/Ri ratios. This is done by investigating the stress distribution along the inner radius of the lug. Next, this study analyses the effects of varying taper angles while maintaining the base width of lug. Lastly, this study modelled cracks along the highest stress location to study the intensity factor of the different lengths of cracks. The BIE2DS programme was used to model cracks at these high stress concentrations and their respective Stress Intensity Factors (SIFs) were calculated after obtaining the crack tip traction for each case. The analysis shows that the orientation of loading and outer-to-inner radius ratio has a noteworthy influence on the SIF and location of the highest stress point. However, varying the taper angle did not have a significant effect on the stress concentration.